2010
DOI: 10.1002/srin.201000207
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Solid Particles on Liquid Viscosity

Abstract: The viscosities of solid‐liquid mixtures were experimentally determined for silicon oil‐paraffin system at room temperature and solid‐liquid oxide mixture at steelmaking temperature. The use of oil‐paraffin systems was to confirm the results of high temperature measurements, the experimental conditions being very difficult to control. The silicon oil‐ paraffin mixtures behaved Newtonian until the particle fraction reached 0.15. At this fraction, the mixture started deviate from Newtonian flow; though some aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 27 publications
2
42
0
Order By: Relevance
“…(2) Even if Du et al stated that the Einstein-Roscoe equation can be used directly with no modification required, 9) but from Fig. 10, it can be seen that the calculated relative viscosities are much lower than the measured values.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(2) Even if Du et al stated that the Einstein-Roscoe equation can be used directly with no modification required, 9) but from Fig. 10, it can be seen that the calculated relative viscosities are much lower than the measured values.…”
Section: Discussionmentioning
confidence: 98%
“…By comparing the measured viscosities with the calculated viscosities by different models, Du et al concluded that Einstein-Roscoe equation was the only model applicably for the systems of Liquid-2CaO.SiO 2 mixtures and liquid-MgO mixtures at the steelmaking temperature, and no modification of the model parameter was found necessary, though the particles were not spherical. 9) However, both Wright et al 7) and Seok et al 8) found that the parameters of Einstein-Roscoe equation should be adjusted to describe the viscosity variation behavior of suspension system.…”
Section: Introductionmentioning
confidence: 99%
“…As Figure 2.27 shown, Wu construct a series study of paraffin/silicon oil system under room temperature condition. The particle size ranges from 150 um to 450 um reported similar results, which is only slightly derivate 1.2% [9]. Konijn constructs viscosity measurement of glycerine/polymethylmethacrylate system and also reported that the particle size did not impact on the suspension viscosity [167].…”
Section: Effects Of Particle Sizesupporting
confidence: 67%
“…For silicate melts, at high-temperature condition, Wu discovered that the slag will become shear thinning fluid above 15% solid fraction [9]. The viscosity of suspension system will be reviewed in Section 2.5.…”
Section: Liquid Viscosity Definitionmentioning
confidence: 99%
“…The phase fraction of SP is derived according to the following equation: [16]. Solids have in general much higher impact on viscosity than minor alteration of, for instance, the slag composition [21]. In the present study, the effect of temperature on the phase fraction of SP in the solid-liquid mixture is negligible in the temperature range of 1573-1773 K. The temperatures within this range could therefore be expected to have a relatively small impact on the slag fluidity and thereby the V extraction.…”
Section: Temperature Impact On the Phase Relationsmentioning
confidence: 99%